Perspectives on Games, Computers, and Mental Health: Questions about Paradoxes, Evidences, and Challenges - Desseilles, Martin (Frontiers in Psychiatry, 2016)
In the field of mental health, games and computerized games present questions about paradoxes, evidences, and challenges. This perspective article offers perspectives and personal opinion about these questions, evidence and challenges with an objective of presenting several thought-provoking ideas and issues in this rapidly developing field. First, games raise some questions in the sense of the paradox between a game (in French, jeu) and an issue (in French, enjeu), as well as the paradox of using an amusing game to treat a serious pathology. Second, games also present evidence in the sense that they involve relationships with others, as well as learning, communication, language, emotional regulation, and hedonism. Third, games present challenges, such as the risk of abuse, the critical temporal period that may be limited to childhood, their important influence on sociocognitive learning and the establishment of social norms, and the risk of misuse of games.